A ligand design strategy to enhance catalyst stability for efficient formic acid dehydrogenation. Issue 15 (20th March 2023) - Guo, Jian; Li, Maoliang; Yin, Chengkai; Li, Xiaobin; Wang, Yilin; Yuan, Jingcheng; Qi, Tiangui
Abstract : Ligand modifications for a previously reported type of Ir catalyst for formic acid dehydrogenation were achieved using a sulfonamide group. The modified catalysts exhibit better stability in air. Abstract : New Ir complexes bearing N -(methylsulfonyl)-2-pyridinecarboxamide (C1 ) and N -(phenylsulfonyl)-2-pyridinecarboxamide (C2 ) were employed as catalysts for aqueous formic acid dehydrogenation (FADH). The ligands were designed to maintain the picolinamide skeleton and introduce strong sigma sulfonamide moieties. C1 and C2 exhibited good stability towards air and concentrated formic acid (FA). During 20 continuous cycles, C1 and C2 could achieve the complete conversion of FA with TONs of 172 916 and 172 187, respectively. C1 achieved a high TOF of 19 500 h −1 at 90 °C and an air-stable Ir–H species was observed by 1 H NMR spectroscopy.